Factors of unsuccessful participation of mothers on labour market during parent leave - Škroudová, Kateřina; Szabová, Lucia; Doležalová, Antonie, 1966-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2012)
Participation on labour market should be automatic part of everyone's life. The same obvious part of everyone's life should be to start a family, which is connected with parent leave. My theses engages in problems of participation of mothers on parent leave on labour market. The current situation of women on parent leave will be analyse by qualitative analysis. The results of this analysis help to identify the factors, why mothers are unsuccessful in participation on labour market during parent leave. I would like to find out if participation on labour market is influenced by family social status or by amount of income from last employment or by age. The theses investigates if employers are opened to employ mothers on parent leave. The focus is also on terminology of labour market. It will be analyse which possibilities the mothers have on the czech labour market and this market will be compared with foreign developed labour markets.
Vedoucí práce: Lucia Szabová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: národní hospodářství [obor bakal. práce]; bakalářské práce; bachelor's theses